2020
DOI: 10.1017/s0950268820002551
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown measures and relative changes in the age-specific incidence of SARS-CoV-2 in Spain

Abstract: During the first months of the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) epidemic in 2020, Spain implemented an initial lockdown period on 15 March followed by a strengthened lockdown period on 30 March when only essential workers continued to commute to work. However, little is known about the epidemic dynamics in different age groups during these periods. We used the daily number of coronavirus 2019 cases (by date of symptom onset) reported to the National Epidemiological Surveillance Netw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(23 reference statements)
2
2
0
1
Order By: Relevance
“…As for those population subgroups which were affected, as with others [17], we observed that individuals who were aged between 20-59 years were over-represented in Estonia (>30%) relative to their proportion in the general population (26%). Again as with others [18,19], we observed an age-group prevalence shift from individuals who were aged forty and above during the first waves of the pandemic to individuals who were below forty, with the most substantial increase being seen during the Omicron waves in individuals who were aged nineteen and below. We could speculate that such shifts can be attributed to several measured and non-measured factors, such as asymptomatic infections and/or milder symptoms in testing younger people, the early vaccination of older at-risk age groups when compared to people in the younger age groups, and public health efforts to manage the pandemic, to mitigation measure enforcement, and also to comply with such measures.…”
Section: Plos Onesupporting
confidence: 89%
“…As for those population subgroups which were affected, as with others [17], we observed that individuals who were aged between 20-59 years were over-represented in Estonia (>30%) relative to their proportion in the general population (26%). Again as with others [18,19], we observed an age-group prevalence shift from individuals who were aged forty and above during the first waves of the pandemic to individuals who were below forty, with the most substantial increase being seen during the Omicron waves in individuals who were aged nineteen and below. We could speculate that such shifts can be attributed to several measured and non-measured factors, such as asymptomatic infections and/or milder symptoms in testing younger people, the early vaccination of older at-risk age groups when compared to people in the younger age groups, and public health efforts to manage the pandemic, to mitigation measure enforcement, and also to comply with such measures.…”
Section: Plos Onesupporting
confidence: 89%
“…In Spain, using the same methodology as in [17], it was shown that during the initial lockdown period, when non-essential work was allowed, individuals aged 40-64 years had a higher relative incidence of infection compared with the pre-lockdown period. However, during the later strengthened lockdown, older adolescents and younger adults had an increased relative incidence in SARS-CoV-2 infection [22]. Our results, together with these observations, highlight the fact that control measures during a pandemic have differential effectiveness in different age groups.…”
Section: Discussionsupporting
confidence: 55%
“…También Backer et al [2] han comunicado como estas medidas comportaban una reducción de los contactos comunitarios de entre 3,7-12,5 personas/individuo y una disminución global de los mismos del 71%; además esta reducción era mayor en los niños y menor en las personas de mas de 80 años. Por su parte De Salazar et al [17] en nuestro país han comprobado como las medidas de restricción social han afectado de modo diferente a los distintos grupos de edad, siendo los mas afectados los mayores de 60 años, generalmente mas cumplidores de estas restricciones.…”
Section: Materials Y Métodosunclassified